Pengembangan buku pedoman lab alam Fakultas Ilmu Sosial untuk Siswa SMP - Nurul Ratnawati; Sukamto Sukamto; I Nyoman Ruja; Neni Wahyuningtyas (Universitas Negeri Malang, 2017)
Purpose of this research is to produce guidelines for the use of natural labs Faculty of Social Sciences to be used by junior high school students as supplement in learning IPS Class VII semester 1. The research method used in this research is research & development with 4- D (four D models). The model consists of four stages: define, design, develop, and disseminate. Book eligibility is validated by material experts and instructional media. Experimental material validation score of 87.96% and expert media learning validation score of 91.66%. Based on these results, it can be saved KeywordsGuidelines, Natural Labs http://dx.doi.org/10.17977/um022v2i22017p061